Desain Model Baitul Maal Santri sebagai Pengelolaan Keuangan Syariah di Pondok Pesantren - Muhtadi, Ridan; Zaenol Hasan; Mohammad Zainal (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: This study aims to develop a Baitul Maal model for Islamic boarding school students (Baitul Maal Santri/BMS) to enhance financial management within these institutions, using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. Research Methods: The research employs primary and secondary data collected through observations and questionnaires distributed to students, administrators, and stakeholders in Islamic boarding schools in East Java. The data are analyzed using SWOT to identify internal and external factors affecting the implementation of the BMS model. Results: The findings reveal strengths such as adherence to sharia principles, avoidance of usury, and facilitating student payments. However, weaknesses include limited human resources, slow collection systems, and inadequate infrastructure. Opportunities include a defined student customer base, strategic location, and a safe environment. Threats include technological advances, limited technological proficiency, and dishonest customers. Conclusion: Based on SWOT analysis, the study recommends strategies focusing on improving human resource capacity, collaborating with financial institutions, and enhancing financial education for students. The BMS model holds significant potential to improve financial literacy and economic skills among students, provided that continuous support from stakeholders is ensured.